Emerging Trends in Phosphorene Fabrication towards Next Generation Devices. Issue 6 (7th February 2017) - Dhanabalan, Sathish Chander; Ponraj, Joice Sophia; Guo, Zhinan; Li, Shaojuan; Bao, Qiaoliang; Zhang, Han
Abstract : The challenge of science and technology is to design and make materials that will dominate the future of our society. In this context, black phosphorus has emerged as a new, intriguing two‐dimensional (2D) material, together with its monolayer, which is referred to as phosphorene. The exploration of this new 2D material demands various fabrication methods to achieve potential applications— this demand motivated this review. This article is aimed at supplementing the concrete understanding of existing phosphorene fabrication techniques, which forms the foundation for a variety of applications. Here, the major issue of the degradation encountered in realizing devices based on few‐layered black phosphorus and phosphorene is reviewed. The prospects of phosphorene in future research are also described by discussing its significance and explaining ways to advance state‐of‐art of phosphorene‐based devices. In addition, a detailed presentation on the demand for future studies to promote well‐systemized fabrication methods towards large‐area, high‐yield and perfectly protected phosphorene for the development of reliable devices in optoelectronic applications and other areas is offered. Abstract : The degradation encountered in realizing few‐layered black phosphorus and phosphorene devices is reviewed. In particular, a detailed presentation of the demand for future studies to promote well‐systemized fabrication methods towards large‐area, high‐yield and perfectly protected phosphorene for the development of reliable devices in optoelectronic applications and other areas is offered.